Bedtime smart phone usage and its effect on student's academic performance - Ting, Zhe Wei (2022)
Mobile device had become an indispensable and effective tool for everyone to interact with others around the world. The evolution of mobile device appears many students rather than workers in every single day, this represented there might some factors of cause poor academic performance of student due to the addiction use of smartphone such as social media, short- messaging and mobile-based game during their sleeping time. This research is investigated to study the effect of bedtime smartphone usage on the academic performance of student which according to their sleep, cognitive function and daily smartphone use. A sample of 103 UTAR students will be selected to answer the online questionnaire. After that, analyse the data by using Statistical Package for the Social Sciences (SPSS) and examine the result of data. Before starting the research formally, the pilot studying for survey should be conducted in this project to assess the reliability of the variables and items in the questionnaire. 36 students were selected for this pilot study and the tool used for testing reliability which is SmartPLS to generate the model and analyse the data which have been collected.